2011
DOI: 10.1100/2011/752790
|View full text |Cite
|
Sign up to set email alerts
|

Pro- and Antiapoptotic Markers in Upper Tract Urothelial Carcinoma Associated with Balkan Endemic Nephropathy

Abstract: The role of aristolochic acid in the etiology of Balkan endemic nephropathy (BEN) and associated upper-tract urothelial carcinoma (UTUC) has been recently confirmed. The aim of this study was to determine apoptosis-related marker(s) specific for BEN-associated UTUC. Present investigation included 105 patients with UTUC, 44 from BEN region and 61 control tumors. Altered expression of Survivin was more often present in BEN UTUC with high grade and solid growth (P < 0.005; P < 0.05) than in control tumors. Signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…The mean age was 61.62 years for the BUC cases and 52.43 years for the normal bladder cases. Histological sections were stained with hematoxylin and eosin (H&E) and were used to estimate the histological grade and pathologic stage 23,24. The 56 normal controls were removed from normal bladder tissues adjacent to neoplastic lesions and were confirmed from the H&E-stained slides as normal bladder tissues without cancer cells.…”
Section: Methodsmentioning
confidence: 99%
“…The mean age was 61.62 years for the BUC cases and 52.43 years for the normal bladder cases. Histological sections were stained with hematoxylin and eosin (H&E) and were used to estimate the histological grade and pathologic stage 23,24. The 56 normal controls were removed from normal bladder tissues adjacent to neoplastic lesions and were confirmed from the H&E-stained slides as normal bladder tissues without cancer cells.…”
Section: Methodsmentioning
confidence: 99%
“…The results presented here suggest that the concentration of survivin is significantly higher in the plasma and urine of BEN patients. Previous articles concerning the expression of surviving in UC tissue specimens of BEN patients reported increased immunohistochemical expression of survivin as the most prominent marker of cancer of urothelial cells in BEN [ 22 , 25 , 26 ]. By exploring the Kaplan–Meier survival curves it was documented that increased survivin expression has a significantly shorter time for disease progression and development of metastases when compared to patients with normal survivin expression [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vascular endothelial growth factor is a pro-angiogenic molecule and an important prognostic marker in UC. Our previous analyses concerned with the expression of both angiogenic growth factors and their receptors revealed that only VEGFR1 could be a significant discriminating factor between cancers of urothelial cells in BEN and non-BEN cancers [ 25 ]. The expression and concentration of VEGF and its receptor (VEGFR) in BEN patients was not significantly different from the controls ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations